পথে চলে যেতে যেতে - চক্রবর্তী, রমা (ঢাকা : আনন্দ, 2004)
Autobiography of a 20th century Bengali woman editor, and author from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Editors -- Bangladesh -- Biography; Authors, Bengali -- 20th century -- Biography; Authors, Bengali -- Bangladesh -- Biography; Bengali literature